Plectin controls biliary tree architecture and stability in cholestasis - Jirouskova, Marketa; Nepomucka, Katerina; Oyman-Eyrilmez, Gizem; Kalendova, Alzbeta; Havelkova, Helena; Sarnova, Lenka; Chalupsky, Karel; Schuster, Bjoern; Benada, Oldrich; Miksatkova, Petra; Kuchar, Martin; Fabian, Ondrej; et al. (Journal of hepatology, 2018)
BACKGROUND & AIMS: Plectin, a highly versatile cytolinker protein, controls intermediate filament cytoarchitecture and cellular stress response. In the present study, we investigate the role of plectin in the liver under basal conditions and in experimental cholestasis. METHODS: We generated liver-specific plectin knockout (PleΔalb) mice and analyzed them using two cholestatic liver injury models: bile duct ligation (BDL) and 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) feeding. Primary hepatocytes and a cholangiocyte cell line were used to address the impact of plectin on keratin filament organization and stability in vitro. RESULTS: Plectin deficiency in hepatocytes and biliary epithelial cells led to aberrant keratin filament network organization, biliary tree malformations, and collapse of bile ducts and ductules. Further, plectin ablation significantly aggravated biliary damage upon cholestatic challenge. Coincidently, we observed a significant expansion of A6-positive progenitor cells in PleΔalb livers. After BDL, plectin-deficient bile ducts were prominently dilated with more frequent ruptures corresponding to an increased number of bile infarcts. In addition, more abundant keratin aggregates indicated less stable keratin filaments in PleΔalb hepatocytes. A transmission electron microscopy analysis revealed a compromised tight junction formation in plectin-deficient biliary epithelial cells. In addition, protein profiling showed increased expression of the adherens junction protein E-Cadherin, and inefficient upregulation of the desmosomal protein desmoplakin in response to BDL. In vitro analyses revealed a higher susceptibility of plectin-deficient keratin networks to stress-induced collapse, paralleled by elevated activation of p38 MAP kinase. CONCLUSION: Our study shows that by maintaining proper keratin network cytoarchitecture and biliary epithelial stability, plectin plays a critical role in protecting the liver from stress elicited by cholestasis. LAY SUMMARY: Plectin is a cytolinker protein capable of interconnecting all three cytoskeletal filament systems and linking them to plasma membrane-bound junctional complexes. In liver, the plectin-controlled cytoskeleton mechanically stabilizes epithelial cells and provides them with the capacity to adapt to increased bile pressure under cholestasis.
Keywords: hepatocyty; cholestáza; Protein Stability; Male; Mice, Knockout; Biliary Tract; Epithelium; stabilita proteinů; epitel; mitogenem aktivované proteinkinasy p38; Cytolinker; mužské pohlaví; DDC diet; Cholestasis; žlučové ústrojí; Keratin filaments; MAP kinasový signální systém; Keratins; myši knockoutované; Hepatocytes; MAP Kinase Signaling System; Animals; játra; Cell-cell junctions; p38 Mitogen-Activated Protein Kinases; zvířata; Plectin; myši; plektin; Liver; keratiny; Mice; Bile duct ligation